Distribution of FIB-4 index in the general population: analysis of 75,666 residents who underwent health checkups - Aya Sugiyama; Akemi Kurisu; Bunthen E; Serge Ouoba; Ko Ko; Anvarjon Rakhimov; Tomoyuki Akita; Takayuki Harakawa; Toru Sako; Makoto Koshiyama; Takashi Kumada; Junko Tanaka (BMC Gastroenterology, 2022)
Abstract Background Fatty liver is frequently found in a general population, and it is critical to detect advanced fibrosis. FIB-4 index is considered a useful marker for evaluating liver fibrosis but the distribution of FIB-4 index in the general population remains unknown. Methods This cross-sectional study included residents who underwent ultrasonography at health checkups in Hiroshima or Iwate prefectures. The distribution of FIB-4 index in the total study population (N = 75,666) as well as in non-alcoholic fatty liver disease (NAFLD) populations (N = 17,968) and non-drinkers without fatty liver populations (N = 47,222) was evaluated. The distribution of aspartate aminotransferase (AST) levels, alanine aminotransferase (ALT) levels was also evaluated. Results The mean FIB-4 index in the total study population was 1.20 ± 0.63. FIB-4 index ≥ 2.67, which indicates a high risk of liver fibrosis, was found in 16.4% of those aged ≥ 70 years. In the NAFLD population, 58.1% of those in their 60 s and 88.1% of those ≥ 70 years met the criteria for referral to hepatologists by using the recommended FIB-4 index cutoff value (≥ 1.3). The mean FIB-4 index in the NAFLD population (1.12 ± 0.58) was significantly lower than in the non-drinkers without fatty liver (1.23 ± 0.63, p < 0.0001). The non-drinkers without fatty liver tended to have higher AST relative to ALT levels (60.0% with AST/ALT > 1.0), whereas the results in the NAFLD population were opposite (14.8% with AST/ALT > 1.0). AST > ALT resulted in a higher FIB-4 index in non-drinkers without fatty liver due to the nature of FIB-4 index formula. Conclusions The cutoff value of FIB-4 index (≥ 1.3) for triaging the elderly people with fatty liver for referral to hepatologists should be reconsidered to avoid over-referral. Due to the impact of age and characteristics of AST/ALT ratios, there is no prospect of using FIB-4 index for primary screening for liver fibrosis in a general population of unknown presence or absence of liver disease, even though it can be easily calculated using routine clinical indices. It is desired to develop a non-invasive method for picking up cases with advanced fibrosis latent in the general population.